2001
DOI: 10.1093/alcalc/36.6.540
|View full text |Cite
|
Sign up to set email alerts
|

A Follow-Up Survey of Alcohol Consumption and Knowledge in Medical Students

Abstract: We surveyed a medical school's students' drinking habits and knowledge 12 years after a previous survey. In this current survey from two academic years, final year students drank less than second year students did. Women in their second year drank as much as men. Overall, 28% of students drank more than the safe limits; 27% of students were problem drinkers, as measured by the CAGE questionnaire, and 52%, as measured by the AUDIT questionnaire. The proportion of students not drinking any alcohol rose from 6% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
10

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 9 publications
4
32
0
10
Order By: Relevance
“…Although greater knowledge was noted in the 4th year students compared with the 2nd year (57.4% vs 48.5%), final year students still had a score lower than 70%; this compares with the findings of Cape et al (17), who reported a significant increase in scores from 23.4% in the 2nd year to 71.8% in the final year of medical education. In our study, the greatest gaps in knowledge related to alcohol, classification, the upper limit for drinking, alcohol-drug interaction and the effects of heavy drinking, similar to findings by other researchers (17,28). Medical curricula were not examined in this study, nevertheless these findings raise concern about the adequacy of preparation of medical students in managing alcohol abuse.…”
Section: Discussionsupporting
confidence: 83%
“…Although greater knowledge was noted in the 4th year students compared with the 2nd year (57.4% vs 48.5%), final year students still had a score lower than 70%; this compares with the findings of Cape et al (17), who reported a significant increase in scores from 23.4% in the 2nd year to 71.8% in the final year of medical education. In our study, the greatest gaps in knowledge related to alcohol, classification, the upper limit for drinking, alcohol-drug interaction and the effects of heavy drinking, similar to findings by other researchers (17,28). Medical curricula were not examined in this study, nevertheless these findings raise concern about the adequacy of preparation of medical students in managing alcohol abuse.…”
Section: Discussionsupporting
confidence: 83%
“…The AUDIT has also been administered in several studies using university students as respondents (e.g. Andersson et al 2007;Fleming, Barry and MacDonald 1991;Granville-Chapman, Yu and White 2001;Kypri et al 2002;McShane and Cunningham 2003;O'Hare and Sherrer 1999;Shields, Guttmannova and Caruso 2004). Consequently, the AUDIT was used as the preferred measure of drinking behaviour in this study.…”
Section: Measurement Instrumentsmentioning
confidence: 99%
“…Con relación al tiempo de aparición de estos trastornos, los estudios muestran resultados variables, e incluso contradictorios, hay quienes afirman que la prevalencia de SDe y PRCA es mayor en los primeros años de estudios en comparación con lo observado al final de su carrera (4,5) ; mientras que otros señalan que la prevalencia de depresión en estudiantes al inicio de sus carreras es similar a la población general, para luego incrementar y mantenerse elevadas a través del tiempo (6,7) . En relación al alcohol, se ha señalado que el consumo es similar durante los años de estudios preclínicos y clínicos (8) .…”
Section: Depresión Y Consumo De Alcohol En Estudiantesunclassified
“…Los estudiantes universitarios se encuentran permanentemente sometidos a diversos estresores (académicos, económicos, familiares, laborales, entre otros); se conoce que la prevalencia de sintomatología depresiva (SDe) en estudiantes universitarios de Lima Metropolitana es de 13% (1) ; se ha informado además que en estudiantes de ciencias de la salud y estudiantes de Medicina estas prevalencias pueden incrementarse hasta 31,2 y 33,6%, respectivamente (2) . Por otro lado, los problemas relacionados al consumo de alcohol (PRCA), entendiendo este como el consumo de alcohol que implica consecuencias negativas a la persona o en su entorno social (3) , también han sido descritos en estudiantes de Medicina, encontrando prevalencias en estudiantes de primer y último año de 36 y 18% respectivamente (4) .…”
Section: Introductionunclassified